Prevalensi Kejadian Covid-19 pada Anak Kota Padang - Annisa Meliariza; Dewi Susanna (Syntax Literate, 2023)
Covid -19 is a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This disease attacks all ages, from babies and children to the elderly. The clinical characteristics of disease progression and outcome in children and young adults appear to be much milder than in older people. Compared to adults, the number of confirmed children cases is very low and the severity and mortality is even lower. The research design used is a descriptive research design with a sample using secondary data with a total of Covid -19 cases in March 2020 to June 2021 in 3231 cases of children. The results found that the 11-15 age group had the most Covid -19 cases at 30.1%, with the number of cases between women and men almost balanced. The majority of children suffering from Covid -19 do self-isolating treatment with a rate of 81.1% and only 0.7% of children have comorbid diseases. Most of the children domiciled in urban areas are 71.6%, and most of the children as many as 72.8% get transmitted from cluster families. Covid -19 cases in children experienced a spike in October 2020 with the number of cases of 706 children infected with Covid -19. Koto Tangah and Kuranji Villages are recorded as the highest cases of Covid -19 in children with more than 500 cases in each village.